Simulation of Dynamic Processes of Gas Flow in Collector Systems - Leonid Lesovoy; Volodymyr Kuzyk (Energy Engineering and Control Systems)
By using CFD-simulation, plug length simulation of local resistance type plugged tee, which changes the flow direction, using equations of hydrodynamics was carried out. During simulation, velocity of medium in the thread of the collector system in which local input resistance was plugged tee, which changes the flow direction, was measured. Herewith for determination of this velocity and reduction of its distortion collector system simulation at different plug lengths was carried out. Plug lengths of local resistance type plugged tee, which changes the flow direction, where the distortion of flow rate diagram disappears, were determined. The equation for calculating length of the thread of the collector system to the place where distortion of gas flow rate disappears, to the plug length of local resistance type plugged tee, which changes the flow direction was obtained.